2022
DOI: 10.1021/acs.jpcb.2c05117
|View full text |Cite
|
Sign up to set email alerts
|

pH Regulates Ligand Binding to an Enzyme Active Site by Modulating Intermediate Populations

Abstract: Understanding the mechanism of ligands binding to their protein targets and the influence of various factors governing the binding thermodynamics is essential for rational drug design. The solution pH is one of the critical factors that can influence ligand binding to a protein cavity, especially in enzymes whose function is sensitive to the pH. Using computer simulations, we studied the pH effect on the binding of a guanidinium ion (Gdm+) to the active site of hen egg-white lysozyme (HEWL). HEWL serves as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…This binding site is formed by the phosphate oxygen of C31 and the O6 oxygen of the G34 nucleobase. Previous computational studies , have shown that the interoxygen distance of ≈7 Å can facilitate the binding of Gdm + via hydrogen bond formation. Additional hydrogen bonding with the sugar oxygens of A5 and C6 provides increased stability to Gdm + (Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…This binding site is formed by the phosphate oxygen of C31 and the O6 oxygen of the G34 nucleobase. Previous computational studies , have shown that the interoxygen distance of ≈7 Å can facilitate the binding of Gdm + via hydrogen bond formation. Additional hydrogen bonding with the sugar oxygens of A5 and C6 provides increased stability to Gdm + (Figure S4A).…”
Section: Resultsmentioning
confidence: 99%